The Role of Interactive Multimedia on Children’s Character Development and Religiosity - Pintakhari, Benyamin; Siahaan, Vera Herawati; Nguru, Desi Arisandi Laga (International Journal Labs, 2022)
Background: One of the fields that take advantage of the positive impact of the development of information technology in education. The impact of the development of information technology on the field of education is one of them is indicated by the increasingly varied learning methods that are currently widely developed. One of the learning methods that are now starting to be widely developed is the multimedia-based interactive learning method. Aim: This research aims to find out the role of interactive multimedia on the development of children's character and religiosity at GKPB MDC Lippo Cikarang Sunday School. Method: This penelitian is causality research with quantitative method approaches. The population in the study was the parents of 33 samples of the Elim Tabernacle's Faith Victory Church. The sample used in this study was as many as 33 parents of students of Elim Tabernacle Church Victory of Faith as many as 33 samples. Findings: Interactive multimedia has a significant effect directly on the development of character and religiosity in children of GKPB MDC Lippo Cikarang Sunday School.